Consumer affinity to wooden framehouses: a typology of German consumers - Gold, Stefan; Rubik, Frieder (My University, 2009)
This paper presents a cluster analysis defining eight consumer types with regard to their disposition of choosing timber as predominant construction material for newly constructed houses in Germany. This typology is based on findings from a representative survey among the German population about people’s attitudes towards general social issues, environment, wood, forestry, timber as construction material and wooden framehouses. The paper identifies eight consumer types according to their attitudes towards these topics and complements them by specific information about their past and anticipated buying behaviour and their socio-demographic characteristics. Four clusters (47% of the population) can be regarded as promising target groups for framehouse marketing.
Keywords: cluster analysis; construction; consumers; consumer typology; Germany; green marketing; marketing target groups; SCP; sustainable consumption and production patterns; survey; timber; wooden framehouses.